Strategi Komunikasi Bisnis dalam Meningkatkan Kepuasan Pelanggan Pada Jasa Expedisi di Era Digital - Nadiya Fadillah; Sumartono Sumartono (Jurnal Bisnis Inovatif dan Digital, 2024)
The current of globalization has made technological and digital developments change the way business and communication are carried out. The digital era is currently the foundation of the business world and opens up new opportunities, including expedition delivery services or what can be called logistics. The expedition delivery service itself not only plays a role in delivering packages to the customer's hands but also must gain the customer's trust so that the customer has an interest in using the delivery service again. The aim of the research is to determine customer satisfaction in using expedition delivery services. The research used is descriptive qualitative research, using an approach that involves collecting relevant data sources, such as journal articles, books, publications and so on. The research data obtained is then analyzed systematically so that they can be continuous with each other in increasing satisfaction with the use of delivery services.